Vitamin D Deficiency Associated Hyperparathyroidism May Be Related With Impaired Glucose Tolerance Without Any Associations With Cardiovascular Risk Factors (Bangladesh Journal of Medicine, 2022)
Introduction: Secondary hyperparathyroidism due to vitamin D deficiency (VDD) is thought to play a role in glucose homeostasis. The aim of this study was to determine the association of parathormone and vitamin D with prediabetes and its different cardiovascular risk factors.Methods: This crosssectional study was conducted among 117 adults with newly detected prediabetes. Participants were recruited consecutively from the Department of Endocrinology, BSMMU to measure serum 25- hydroxyvitamin D by high performance liquid chromatography, intact parathormone (iPTH) by chemiluminescent enzyme-labeled immunometric assay; fasting insulin by chemiluminescent microparticle immunoassay and glucose by glucose oxidase method to calculate homeostasis model assessment of insulin resistance (HOMA-IR).Results: Patients with hyperparathyroidism had significantly higher percentages of VDD than those with normal parathyroid status. Only percentages of impaired glucose tolerance (IGT) status had significant association with the combined iPTH and vitamin D groups. Serum iPTH significantly correlated with age, HbA1C, vitamin D and HOMA-IR. Hyperparathyroidism had significant predictive association with only IGT and hypovitaminosis D in adults with prediabetes.Conclusion: VDD combined with high PTH may be associated with glycemic dysregulation in adults with prediabetes especially in IGT without any significant associations with its cardiovascular risk factors.Bangladesh J Medicine 2022; 33: 154-160